Where the money goes : understanding litigant expenditures for producing electronic discovery - Pace, Nicholas M. (Nicholas Michael), 1955- (Rand Corporation monograph series., 2012)
Pretrial discovery procedures are designed to encourage an exchange of information that will help narrow the issues being litigated, eliminate surprise at trial, and achieve substantial justice. But, in recent years, some have claimed that the societal shift from paper documents to electronically stored information (ESI) has led to sharper increases in discovery costs than in the overall cost of litigation. The authors employed a case-study method to gather cost data for 57 large-volume e-discovery productions, including those in traditional lawsuits and regulatory investigations; collected information from extensive interviews with key legal personnel from the responding companies; and reviewed the legal and technical literature on e-discovery, with emphasis on the intersection of information-retrieval science and the law. Although the results cannot be generalized to all litigants or even large corporations in particular, the monograph provides a richly detailed account of the resources required by a diverse set of very large companies operating in different industries to comply with what they described as typical e-discovery requests. The monograph also suggests ways to reduce those costs as well as address concerns over duties to preserve data in anticipation of litigation.